(untitled) (Povijesni prilozi (Historical Contributions), 2024)
According to his biographer, Karel van Mander, the Netherlandish painter Jan van Scorel spent a brief period studying with Albrecht Dürer before setting off for Carinthia, where he was warmly received by the local nobility. Historians have long been aware of the commissions from this period of van Scorel’s career – the Adoration of the Magi and the Frangipani-Altar. Originally a triptych, the latter work was “modernized” and, in 1692, encased in a Baroque altar housing in the church of St. Martin in the Carinthian village of Obervellach. The coats of arms on the reverse of the Holy Kinship indicate that the painting was commissioned by Count Christopher Frankapan and his wife Apollonia Lang of Wellenburg. However, over time, art historians have come to assume that the Holy Kinship portrays members of the Lang family, leading to the conclusion that the work was commissioned by Apollonia’s brother, Matthäus Lang von Wellenburg, Cardinal and Prince-Archbishop of Salzburg. However, the backdrop against which the family members are portrayed, featuring the town, new fortress, and castle on the hill, corresponds to Modruš with Tržan-grad, owned at the time by the Frankapan family.